An Application Pre-Conference and Post-Conference in Hospital: a Case Study - Afandi, Alfid Tri; Fauziah, Nur Hasanatil; Asmaningrum, Nurfika; Sujarwanto (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
Pre-conference and post-conference are part of implementing the Professional Nursing Care Model (MAKP) to improve the quality of nursing services in hospitals and minimize negligence or errors in nursing practice. Pre-conference and post-conference is the activity of the team leader and members of the nursing team in communicating related to nursing care given to patients during shift changes. In pre-conference and post-conference, the nurse in charge of care must plan daily activities for patients from admission to discharge from the hospital. However, implementation pre-conference and post-conference still need to be improved. This can affect the nursing care provided by nurses. This writing aims to describe pre-and post-conference activities during the COVID-19 pandemic, which students in the inpatient room carried out. This research uses the case study method. Implementation research results in pre-conference are in a suitable category, while post-conference results could be better. Therefore to optimize the implementation of pre-conference and post-conference, nurses need to improve their quality as Nurses in Charge of Caring (PPJA).